PENGARUH KOMPETENSI DAN PEMAHAMAN TERHADAP PENGELOLAAN APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) DI KABUPATEN NGANJUK - Dwi Puji Rahayu; Ambarwati Ambarwati (STIE Mahardhika, 2022)
This study aims to determine the effect of human resources consisting of competence, and understanding on the management of village financial system application in villages in Nganjuk district. The research method used is a quantitative research method with primary data obtained from questionnaire data which is measured with a likertscale.The population in this study were all villages in Nganjuk district as many as 264 villages, with the respondents being the siskuedes operator, Village secretary and village treasure, while the sample uses the slovin formula, resulting 73 samples.The research data was processed using the classical assumption test consisting of the Normality Test, Multicollinerity Test and Multiple Linear Regression Test. The results of this study conclude that 1) Competence has a positive and significant effect on the management of village finsncialsysten applications in Nganjuk district .It is evidenced by the acquisition of the t – count value greater than t – table with a significant less than 0,05. 2).Understanding has a positive and significan impact on the management of village financial system applications in Nganjuk district. It is evidenced by the acquisition of the t – count value greater than t – table with a significant less than 0,05. 3). Competence and understanding together effect the management of village financial system applications in Nganjuk district. It is proven by the acquisition of the calculated F value that is greater than the F table with a significant less than 0,05